Immune dysregulation in endometrial tuberculosis: elevated HLA-G and IL-1Ra as key modulators - Huang, Dan; Dai, Jinlong; Yu, Haotian; Chen, Wen (Frontiers in Cellular and Infection Microbiology, 2025)
Endometrial tuberculosis (ETB) is a reproductive system infection caused by Mycobacterium tuberculosis, primarily invading the endometrium through hematogenous dissemination. This study included 10 patients diagnosed with ETB and 10 patients with pulmonary tuberculosis (PTB) to analyze their clinical, pathological, and immunological characteristics. Anatomically, PTB presented the highest prevalence among tuberculosis cases. Compared to PTB imaging, CT scans of ETB showed less distinctive diagnostic features. Pathologically, abscess formation was more frequently observed in ETB patients than in PTB patients, suggesting a more intense local inflammatory response in ETB. However, there were no statistically significant differences in granulomatous lesions, caseous necrosis, coagulative necrosis, inflammatory necrosis, exudation, acute inflammation, or fibrous tissue hyperplasia between the two groups. Immunohistochemical analysis revealed higher infiltration of macrophages (CD68) in ETB lesions compared to PTB, whereas the counts of T cells (CD3+, CD4+, CD8+) and B cells (CD20) showed no significant differences. Notably, the expression levels of HLA-G and IP-10 were significantly elevated in the lesion areas of ETB compared to PTB. Similarly, the expression of HLA-G, IP-10, IL-1Ra, and IL-10 was significantly higher in the ETB group than in the PTB group. Furthermore, HLA-G and IL-1Ra expression levels were markedly elevated in ETB lesion areas compared to surrounding normal endometrial tissue. HLA-G plays a pivotal role in immune tolerance by modulating local immune responses, while IP-10 is involved in chronic inflammatory signaling. IL-1Ra and IL-10 are key regulators of endometrial immune homeostasis, counterbalancing inflammatory responses that could otherwise disrupt reproductive function. These immunoregulatory factors are crucial in maintaining immune tolerance within the endometrium and may influence immune responses associated with endometrial tuberculosis.